(untitled) (KULT_online, 2016)
Efrat Gal-Ed´s book is an extensive biographical work on the Yiddish poet Itzik Manger. Gal-Ed discusses his work and life, situating him in the broader context of linguistic and ethnic developments of the 20th century. The author presents Manger as a European poet, engaged in the European cultural developments, who simultaneously was a poet of unrecognized minority language. This biography of Manger contributes both to literary and Jewish studies.